Comparison of the Effects of Oral Midazolam and Intranasal Dexmedetomidine on Preoperative Sedation and Anesthesia Induction in Children Undergoing Surgeries - Cai, Yu-Hang; Wang, Cheng-Yu; Li, Yang; Chen, Jia; Li, Jun; Wu, Junzheng; Liu, Hua-Cheng (Frontiers in Pharmacology, 2021)
Background and Purpose: Premedication with either oral midazolam or intranasal dexmedetomidine prior to surgery remains less than ideal. The aim of this study was to investigate whether the combination of those two drug regimens would have any beneficial effects on the preoperative sedation and the children’s compliance during anesthesia inhalation induction. Experimental Approach: One hundred thirty-eight children aged 2–6 years were randomly allocated into three groups: Group M with oral midazolam 0.5 mg kg−1, Group D with intranasal dexmedetomidine 2 μg kg−1, and Group M + D with intranasal dexmedetomidine 1 μg kg−1 plus oral midazolam 0.5 mg kg−1. The primary outcome was the children’s compliance during inhalation induction with sevoflurane. The secondary outcomes included the preoperative sedative effects, behavior scores, parental separation anxiety scores, and the postoperative incidence of emergence agitation and recovery time. Results: Subjects in Group M + D showed higher satisfaction scores of compliance (p = 0.0049) and mask acceptance (MAS) (p = 0.0049) during anesthesia inhalation induction. Subjects in Group M + D had a significantly shorter time than those in Groups M and D to achieve the desired sedation level (p < 0.001) and remained at a higher sedation score in the holding area and up to the anesthesia induction after drug administration (p < 0.001). Conclusion and Implications: We conclude that pediatric patients premedicated with intranasal dexmedetomidine 1 μg kg−1 plus oral midazolam 0.5 mg kg−1 had significantly improved anesthesia induction compliance, and quicker onset to achieve and maintain a satisfactory level of sedation than those premedicated separately with two drugs. Therefore, the combined premed regimen is a greater choice when we are expecting a higher quality of sedation and a smoother anesthesia induction in children undergoing the surgeries.